2016
DOI: 10.1128/msphere.00039-16
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Putative Translocated Effector Proteins of the Edwardsiella ictaluri Type III Secretion System

Abstract: The bacterial pathogen Edwardsiella ictaluri causes enteric septicemia of catfish (ESC), an economically significant disease of farm-raised channel catfish. Commercial catfish production accounts for the majority of the total fin fish aquaculture in the United States, with almost 300,000 tons produced annually, and ESC is the leading cause of disease loss in the industry. We have demonstrated the survival and replication of E. ictaluri within channel catfish cells and identified a secretion system that is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…Closely related to E. tarda, Edwardsiella ictaluri is another fish pathogen that multiplies within the Edwardsiella ictaluri-containing vacuole (EiCV). The EiCV demonstrates an initial acidification and subsequent neutralization, which leads to the translocation of effectors into the host cytosol (37)(38)(39). Although it remains to be determined if EtCVs and EiCVs display similar pH dynamics during their maturation, we believe that the EsaB/EsaL/EsaM complex ensured proper function of the T3SS at acidic pH and is ideal for E. tarda to adapt to its intracellular life.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Closely related to E. tarda, Edwardsiella ictaluri is another fish pathogen that multiplies within the Edwardsiella ictaluri-containing vacuole (EiCV). The EiCV demonstrates an initial acidification and subsequent neutralization, which leads to the translocation of effectors into the host cytosol (37)(38)(39). Although it remains to be determined if EtCVs and EiCVs display similar pH dynamics during their maturation, we believe that the EsaB/EsaL/EsaM complex ensured proper function of the T3SS at acidic pH and is ideal for E. tarda to adapt to its intracellular life.…”
Section: Discussionmentioning
confidence: 94%
“…However, this complex dissociates at neutral pH, triggering the secretion of effectors but not translocon proteins. Similar to Salmonella, Edwardsiella ictaluri, a fish pathogen that shares a common virulence strategy with E. tarda (35)(36)(37), resides in E. ictaluri-containing vacuoles (EiCVs) that undergo an initial acidification and subsequent neutralization, ultimately leading to the translocation of effectors into the host cytosol (37)(38)(39). We hypothesized that a pH shift might also trigger the secretion of effectors by the E. tarda T3SS.…”
Section: Figmentioning
confidence: 99%
“…It has been shown that E. ictaluri Type III Secretion System (T3SS) is tightly regulated and expressed inside the catfish macrophages (Rogge & Thune, 2011). The T3SS effector proteins secreted into macrophages manipulate the pathways of host cells (Dubytska, Rogge, & Thune, 2016;Zhao et al, 2013), and deletion of them impairs the intracellular replication of E. ictaluri (Thune et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…All 9 putative effectors appeared to be absent from the genomes of E. hoshinae ATCC33379 and E. tarda ATCC15947 (Tables 1 and S2). Furthermore, of the reported list of 9 effectors in E. ictaluri, only EseG and EseN are shared by E. piscicida, and the remaining 7 effectors are absent in all the other species, 55 suggesting a specific basis for the evolution of pathogenic mechanisms and host specificity in the evolutionary history of these Edwardsiella species.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dubytska et al identified 9 putative T3SS effectors using bioinformatics and a cyaAbased translocation assay. 55 Of these 9 effectors, 5 contain leucine-rich repeat protein (LRR) domains with various numbers of repeats. Interestingly, stringent BLASTP analysis indicated that, among the 9 effectors identified here, ETAE_3282 is not found in the published E. ictaluri genomes.…”
Section: Discussionmentioning
confidence: 99%